Pendidikan Sains Berbasis Praktik, SSI, dan Stem–CT sebagai Mesin Pendorong Kompetensi Masa Depan Siswa Sekolah Dasar: Sebuah Kajian Pustaka - Yusak Ratunguri; I Wayan Suastra; I Made Citra Wibawa; Ida Bagus Putu Arnyana (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to examine how science education grounded in scientific practices, socioscientific issues (SSI), and the integration of STEM–Computational Thinking (CT) can foster future competencies among elementary school students. The method employed is a literature review analyzing relevant studies on 21st-century science learning, scientific literacy, and technology integration. The findings indicate that when science is taught as an epistemic activity—through inquiry, modeling, and evidence-based argumentation—and connected to meaningful social and environmental contexts, it simultaneously strengthens the 4C skills (critical thinking, creativity, collaboration, and communication), scientific literacy, data-digital literacy, and scientific character. The review also highlights key implementation prerequisites, including curriculum autonomy, formative performance-based assessment, meaningful technological ecosystems, and sustained teacher professional development. In conclusion, science education built upon practice, context, and technology offers a strategic framework for developing cross-domain competencies in elementary education. Keywords: Future Competencies, Scientific Practices, Socioscientific Issues, STEM-CT, Elementary Science Education